'If there were water we should stop and drink': neurofibromatosis presenting with diabetes insipidus. (11th February 2018) - Barry, Rachel; O' Connor, Antoinette; Awang, Mohn Hazriq; O' Toole, Orna
Abstract : A 58-year-old right-handed woman presented to our institution with a 1-month history of polydipsia and polyuria. She had a remote history of neurofibroma excision by dermatology and, on examination, was noted to meet the clinical diagnostic criteria for neurofibromatosis type 1. Laboratory investigations revealed hypernatraemia and elevated serum osmolality, accompanied by reduced urinary osmolality. A subsequent water deprivation test confirmed central diabetes insipidus, which responded to treatment with desmopressin. MRI of the brain showed pituitary enlargement, which raised the possibility of an underlying pituitary adenoma or, alternatively, lymphocytic hypophysitis. Both conditions have rarely been described in neurofibromatosis.